2014
DOI: 10.1590/1809-6891v15i219775
|View full text |Cite
|
Sign up to set email alerts
|

Biometria do bulbo ocular de bovinos da raça Nelore

Abstract: RESUMOObjetivou-se realizar a biometria de componentes do bulbo do olho de bovinos adultos da raça Nelore. Para tal, analisaram-se 121 bulbos oculares de animais abatidos com idade entre dois a três anos em um estabelecimento no município de Itaperuna-RJ, Brasil. Vinte medições macroscópicas foram feitas nos bulbos oculares e suas estruturas. Os bulbos apresentaram eixo óptico medindo 33,27 ± 1,55 mm, diâmetro equatorial de 38,07 ± 1,70 mm e volume estimado de 24,07 ± 3,51 mL. Houve correlação moderadamente po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 10 publications
0
1
0
Order By: Relevance
“…This may be due to differences between the species, as studies on large animals such as cattle (Corrêa et al, 2014;El-Maghraby et al, 1995;Potter et al, 2008) buffaloes (Assadnassab & Fartashvand, 2013), horses (McMullen & Gilger, 2006), donkeys (Laus et al, 2013) and elephants (Bapodra et al, 2010) found different ocular biometry values. In addition, the measurements performed on eyes extracted from carcasses may be imprecise due to post-mortem changes (Corrêa et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…This may be due to differences between the species, as studies on large animals such as cattle (Corrêa et al, 2014;El-Maghraby et al, 1995;Potter et al, 2008) buffaloes (Assadnassab & Fartashvand, 2013), horses (McMullen & Gilger, 2006), donkeys (Laus et al, 2013) and elephants (Bapodra et al, 2010) found different ocular biometry values. In addition, the measurements performed on eyes extracted from carcasses may be imprecise due to post-mortem changes (Corrêa et al, 2014).…”
Section: Discussionmentioning
confidence: 99%